ANALISIS SEMIOTIKA PADA PUISI “PELAYARAN TUHAN” KARYA AFRIZAL MALNA - Thabroni, Gamal; Wikanengsih, Wikanengsih; Kartiwi, Yesi Maylani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is motivated by the difficulty in appreciating a poetry that uses a lot of indexes and symbols that are rarely used and not yet known by the public such as in the work of "Pelayaran Tuhan" by Afrizal Malna. The purpose of this research is (1) Describing the results of a semiotic analysis of “Pelayaran Tuhan” poetry by Afrizal Malna, (2) Summarizing the theme of the poetry based on the analysis results. The method used in this research is descriptive qualitative with Peirce's semiotic approach which divides the signification process of sign into three factors: representamen, object, and interpretant. The results of the study found that this poem tends to use more tangible signs of index objects and symbols, most of which is not a familiar symbols. The system of meaning in this poem uses many imageries and emotions conveyed through index and symbols of sailing and sea atmosphere. The results of the analysis in this research show that this poetry is closely related to the theme of God or religious, spiritual and transcendental.